PENGARUH KONSELING REALITA TERHADAP PEMBENTUKAN KEMANDIRIAN PADA SISWA SMPN 2 KURIPAN - Elis Sulistiya; Jumailiyah Jumailiyah (Universitas Pendidikan Mandalika, 2016)
The purpose of this study was to determine the effect of Reality Counseling on the Establishment of Independence in Students at SMPN 2 Kuripan. The type of experiment used in this research is Pre-experimental Design (non-design) or impure experiment, and one form of the experiment is the One-Group Pretest-Posttest Design. The population in this study were all students of SMPN 2 Kuripan who experienced problems in independence , the sample used was 10 students. In this study, the data collection method used was a questionnaire method as the main method. To analyze data using the t-test formula. The results of the study were: the t value of 4.756 and the t table value at the 5% significance level with N = 10 of 2.262. Thus the t value is greater than the t value in the table (4.756> 2.262) so that it can be concluded